Creating an Association of Southeast Asian Nations payment system: Policy and regulatory issues - Tanai Khiaonarong (Asian Development Bank Institute (ADBI), 2013)
The Association of Southeast Asian Nations (ASEAN) is expected to benefit from the significant growth in the Asia-Pacific payments market. Growth in economic activity would increase the size, scale, and scope of payment transactions. Enabling the scale and scope of payments would in turn increase economic activity. This would also require national payment systems to be regionalized and operate with cross-border and multi-currency capabilities. As existing regional payment arrangements have illustrated how they can be successfully established, ASEAN can itself leverage on its current cooperative forums in creating a more regionalized payment system. In doing so, it faces the following challenges. First, promoting the use of cashless payments would require increased private sector involvement in improving accessibility to basic payment infrastructure, increasing their interoperability, and creating a competitive cross-border retail payment scheme. Second, creating cross-border and multi-currency payment systems could possibly proceed with the interlinking of existing real-time gross settlement systems within the region, and later enlarged, but this would need to be supportive of the broader goals of sequencing financial services liberalization. Third, legal harmonization would need to keep pace with rapid technological and regulatory changes where the introduction of settlement finality legislation is seen as an important precondition to support cross-border payments. Fourth, managing foreign exchange settlement risk would need to be addressed with the growth in global foreign exchange market activities and this would involve the development of risk-reduction features in payment systems. And fifth, enhancing cooperation would involve the creation of regional oversight frameworks and cross-border collateral arrangements as systems become increasingly interconnected and interdependent in the long run.
Keywords: E42; E58; G28; 330; asean; payment system; asia-pacific payments market; national payment systems; Internationaler Zahlungsverkehr; Regionale Wirtschaftsintegration; ASEAN-Staaten